Cost-effectiveness of various immunization schedules with inactivated Sabin strain polio vaccine in Hangzhou, China - Xu, Yuyang; Liu, Yan; Wang, Jun; Che, Xinren; Du, Jian; Zhang, Xiaoping; Gu, Wenwen; Zhang, Xuechao; Jiang, Wei (Frontiers in Public Health, 2022)
Background It is necessary to select suitable inactivated poliovirus vaccine(IPV) and live, attenuated oral poliovirus vaccine (OPV) sequential immunization programs and configure the corresponding health resources. An economic evaluation was conducted on the sequential procedures of Sabin strain-based IPV (sIPV) and bivalent OPV (bOPV) with different doses to verify whether a cost-effectiveness target can be achieved. This study aimed to evaluate the cost-effectiveness of different sIPV immunization schedules, which would provide convincing evidence to further change the poliovirus vaccine (PV) immunization strategies in China. Methods Five strategies were included in this analysis. Based on Strategy 0(S0), the incremental cost (IC), incremental effect (IE), and incremental cost-effectiveness ratio (ICER) of the four different strategies (S1/S2/S3/S4) were calculated based on the perspective of the society. Seven cost items were included in this study. Results of field investigations and expert consultations were used to calculate these costs. Results The ICs of S1/S2/S3/S4 was Chinese Yuan (CNY) 30.77, 68.58, 103.82, and 219.82 million, respectively. The IE of vaccine-associated paralytic poliomyelitis (IEVAPP) cases of S1/S2/S3/S4 were 0.22, 0.22, 0.22, and 0.11, respectively, while the IE of disability-adjusted life-years (IEDALY) of S1/S2/S3/S4 were 8.98, 8.98, 8.98, and 4.49, respectively. The ICERVAPP of S1/S2/S3/S4 gradually increased to CNY 13.99, 31.17, 47.19, and 199.83 million/VAPP, respectively. The ICERDALY of S1/S2/S3/S4 also gradually increased to CNY 0.34, 0.76, 1.16, and 4.90 million/DALY, respectively. Conclusion ICERVAPP and ICERDALY were substantially higher for S3 (four-sIPV) and S4 (replacement of self-funded sIPV based on one-sIPV-three-bOPV). Two-sIPV-two-bOPV had a cost-effectiveness advantage, whereas S2/S3/S4 had no cost-effectiveness advantage.